Examining explanation types given by exhibitionists - Rahime, Jamal (My University, 2015)
Sexual offenders who typically deny or minimize the severity of their actions are often considered unqualified to participate in treatment interventions. Although denial is a significant predictor of poor treatment motivation, the literature also reveals inconsistent findings to demonstrate that denial and minimization is a good predictor of recidivism (Hanson & Morton-Bourgon, 2005). The use of cognitive distortions is considered a common and reasonable defense strategy among most, if not all individuals when we are confronted for doing something wrong. However, when sexual offenders attribute their criminal behaviour to multiple internal and external factors, their explanations are often ignored and they are rejected from treatment (Maruna & Mann, 2006). Nonetheless, previous research has shown that some denying offenders eventually admitted to some or all of their charges after they engaged in a relapse prevention program, and therefore it has been recommended that more research needs to be done on offender denial and minimization (Cooper, 2005). This study investigates the different explanation types given by sexual offenders convicted of exhibitionism and indecent acts. Fifty closed forensic case files were reviewed and coded to create a descriptive record of the offenders’ behavioural characteristics and the different types of explanations given after committing their crimes. Explanations identifying cognitive distortions (e.g., externalizing excuse) rather than absolute admittance of criminal motives were the more common types expressed from the sample. This study is important because it is the first of its kind to examine explanation types in exhibitionists and contributes to our understanding of their excuse-making patterns.
Presented on January 28, 2015 at I, Research: Student Research Week held at MacEwan University in Edmonton, Alberta.
Keywords: sex offenders; denial